2014
DOI: 10.1088/0967-3334/36/1/163
|View full text |Cite
|
Sign up to set email alerts
|

On the risk of aortic valve replacement surgery assessed by heart rate variability parameters

Abstract: In recent years the number of arterial stenosis (AS) patients has grown rapidly and valvular disease is expected to be the next great epidemic. We studied a group of 385 arterial valve replacement (AVR) surgery patients, of whom 16 had died in the postoperational period (up to 30 d after the operation). Each patient had a heart rate variability (HRV) recording made prior to the operation in addition to a full set of medical diagnostics including echocardiography. We formed 16 age, sex, New York Heart Associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Even if the results were promising, particularly in the field of heart rate variability, it is questioned whether a monofractal DFA estimating one or two coefficients may improve health assessment and risk stratification compared to nonfractal methods (Sassi et al, 2015). Therefore, the more advanced research in this field is investigating how DFA can be enhanced by jointly depicting the multifractal and multiscale nature of the time series in order to model pathophysiological mechanisms more completely (Zebrowski et al, 2015; Solinski et al, 2016).…”
Section: Summary Of Advantages and Limitations And Conclusionmentioning
confidence: 99%
“…Even if the results were promising, particularly in the field of heart rate variability, it is questioned whether a monofractal DFA estimating one or two coefficients may improve health assessment and risk stratification compared to nonfractal methods (Sassi et al, 2015). Therefore, the more advanced research in this field is investigating how DFA can be enhanced by jointly depicting the multifractal and multiscale nature of the time series in order to model pathophysiological mechanisms more completely (Zebrowski et al, 2015; Solinski et al, 2016).…”
Section: Summary Of Advantages and Limitations And Conclusionmentioning
confidence: 99%
“…Filipovic et al [ 74 ] found a higher risk of death 30 days after major non-cardiac surgery in patients with preOP LF/HF < 2.0. Zebrowski et al [ 75 ] did not find significant differences in LF, HF, and LF/HF between patients who died within 30 days after aortic valve surgery, and those who survived. They did however find higher rMSSD (p = 0.0054) in the group that died, along with differences in other time domain analyses (lower Guzik’s, Porta’s, and Ehler’s index and higher index D) [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zebrowski et al [ 75 ] did not find significant differences in LF, HF, and LF/HF between patients who died within 30 days after aortic valve surgery, and those who survived. They did however find higher rMSSD (p = 0.0054) in the group that died, along with differences in other time domain analyses (lower Guzik’s, Porta’s, and Ehler’s index and higher index D) [ 75 ]. The two studies did not specify when in the preOP course HRV measurements were taken.…”
Section: Resultsmentioning
confidence: 99%
“…KLD was calculated only for the nighttime recordings of the heart rhythm. Because of the different time for every patient for going to sleep, for each case the period of observation was selected using the average RR value over time (Gierałtowski et al, 2012;Żebrowski et al, 2015). These records were also analyzed with the use of windows (the tested signal was divided into adjacent, non-overlapping windows).…”
Section: Methodsmentioning
confidence: 99%